Nocturnal desaturation in patients with non-operable chronic thromboembolic pulmonary hypertension - Yu Taniguchi; Miki Sakamoto; Hiroyuki Fujii; Keisuke Miwa; Yasunori Tsuboi; Kenichi Yanaka; Noriaki Emoto; Hiromasa Otake (BMC Pulmonary Medicine)
Abstract Background Nocturnal desaturation is occasionally observed in patients with chronic thromboembolic pulmonary hypertension (CTEPH) despite the absence of parenchymal lung disease; however, the underlying mechanism remains unclear. This study aimed to clarify the clinical features of nocturnal desaturation in patients with CTEPH. Methods Data of 163 patients with CTEPH who underwent balloon pulmonary angioplasty (BPA) between March 2011 and December 2022 were retrospectively analyzed. We evaluated their hemodynamics using right heart catheterization, arterial blood gas examination, respiratory function tests, nocturnal oximetry, and cardiopulmonary exercise testing, which were routinely performed at baseline and after BPA. Results A higher ratio of dead space to tidal volume (VD/VT) (p < 0.001) and higher alveolar-arterial oxygen difference (A-aDO2) (p = 0.026) at baseline were associated with greater nocturnal desaturation in the multivariable linear analysis. After BPA, nearly normal hemodynamics was achieved (mean pulmonary arterial pressure: 37.5 ± 10.0 to 20.2 ± 4.9 mmHg, p < 0.01). Nocturnal desaturation also improved from − 13.3 ± 5.8% at baseline to -10.3 ± 5.4% after BPA (p < 0.01). Improvement in VD/VT correlated well with improvement in nocturnal desaturation after BPA (p < 0.001, R2 linear = 0.18). Conclusions Nocturnal desaturation often coexists with CTEPH. VD/VT, a marker of physiologic dead-space fraction, A-aDO2, a marker of ventilation-perfusion mismatch, and lung diffusing capacity were strongly associated. Nocturnal desaturation improved slightly after BPA, which was associated with a decrease in the physiological dead- space fraction. Our study emphasizes the importance of including nocturnal oximetry in routine evaluations and continuation of nocturnal oxygen therapy, if necessary, in patients with CTEPH.